2014
DOI: 10.1051/0004-6361/201321555
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic structure of massive star-forming regions

Abstract: Context. The mid-and far-infrared view on high-mass star formation, in particular with the results from the Herschel space observatory, has shed light on many aspects of massive star formation. However, these continuum studies lack kinematic information. Aims. We study the kinematics of the molecular gas in high-mass star-forming regions. Methods. We complemented the PACS and SPIRE far-infrared data of 16 high-mass star-forming regions from the Herschel key project EPoS with N 2 H + molecular line data from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 84 publications
6
53
0
Order By: Relevance
“…3. This correlation, and the fact that this peak has the same velocity as seen in N 2 H + 1→0 (Tackenberg et al 2014), provides evidence that this high column density clump is clearly an intrinsic part of the IRDC.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…3. This correlation, and the fact that this peak has the same velocity as seen in N 2 H + 1→0 (Tackenberg et al 2014), provides evidence that this high column density clump is clearly an intrinsic part of the IRDC.…”
Section: Resultssupporting
confidence: 58%
“…the strongest submm-continuum sources from ATLASGAL (Contreras et al 2013;Csengeri et al 2014) and two positions off-source but within the cloud. The continuum sources were also observed in the optically thin N 2 H + 1→0 line at 93.173 GHz with a velocity resolution of 0.2 km s −1 (Tackenberg et al 2014), and the centre velocities reported in their Table 3 are indicated as a dashed blue line in Fig. 8.…”
Section: Collapse Signatures In Molecular Line Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Case studies of massive cluster progenitors show evidence both for global collapse and for flows of dense gas (e.g. Schneider et al 2010;Csengeri et al 2011a,b;Peretto et al 2013;Tackenberg et al 2014). This points to a scenario where massive clumps undergo star formation, while gas replenishment arrives on larger scales, and maintains the observed similar mass range for these clumps.…”
Section: Stability Estimates and Timescalesmentioning
confidence: 96%